Effects of the MIND&GAIT physical exercise programme on depressive symptoms in institutionalised frail older adult: A Pilot Study - Nuno Rafael Pedro do Couto; Adriana Silva; Francisca Duarte; Luís Cid; Teresa Bento; Rita Santos Rocha; João Brito; Anabela Vitorino (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The main purpose of this study was to analyse the effects of MIND&GAIT, a physical exercise programme, on depressive symptoms in frail institutionalised older people.  Through a pilot study, thirty-five Portuguese frail older people (19 female, 16 male), with a mean age of 83.45 ± 9.73 years, participated in this study. The participants were randomly assigned into an experimental group (n = 19) and a control group (n = 16). Intervention was based on MIND&GAIT, physical exercise programme for frail older people. Depressive symptomatology was assessed using the Beck Depression Inventory (BDI-II) before and after 12 weeks of intervention. Results showed significant differences in depressive symptoms between the experimental group and the control group after the intervention. Depressive symptomatology decreased in the experimental group, while the participants in the control group had a significant increase in this indicator at the post-intervention moment. In general, the older people who were involved in the intervention group, improved their depressive symptoms, and the older who did not participate in the MIND&GAIT physical exercise programme, worsen this indicator. Considering the present results, we can conclude that this pilot study has presented initial findings that MIND&GAIT can contribute to improving depressive symptomatology in this population. This study has yielded essential data to construct subsequent randomized-controlled trials that can be effectively and feasibly executed within the community.